Systematic Review: Information Exposure on Family Planning Associated with Contraceptive Use - Kholidil Amin; Purwanti Hadisiwi; Jenny Ratna Suminar (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education)
Background: The use of contraceptive methods by couples of childbearing age can be influenced by the information received on Family Planning (FP). FP information can be received or accessed from various sources or channels such as electronic and printed mass media, promotional media (posters and leaflets), social media, and even face-to-face communication with certain parties who understand FP. Several studies have discussed it. Objective: Using a Systematic Literature Review and Meta-Analysis, this study seeks to present logical evidence from the published literature regarding the relationship and effect of information exposure about FP on contraceptive use. Method: Literature searches were performed on the Scopus indexing engine and the PubMed database using several keywords such as "FP message”, "FP communications”, and "media exposure and FP”. Studies should have specified criteria, such as they were published between January 2015 and December 2020, and the research locations were either in Indonesia or abroad. Results: The search results found 742 studies, and 22 studies were selected. Based on the review process, the relationship and effect of exposure to FP information on contraceptive use could be mapped through communication channels in general, namely mass media exposure about FP information, and specific communication channels, namely exposure to FP information through television, radio, print media, digital communication, and face-to-face communication. Conclusion: The use of contraceptive methods, both modern and non-modern, was strongly influenced by FP information received by couples of childbearing age; however, some information channels proved insignificant. Therefore, further researchers can follow up on several recommendations based on this result. Various communication channels in delivering FP messages or information remain a determining factor that must be considered by further researchers, given the rapid development of media such as online media.